2011
DOI: 10.1021/mz200075x
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Diffusion of Polyelectrolyte Chains within Multilayer Films

Abstract: We have found diffusion of polyelectrolyte chains within multilayer films to be highly anisotropic, with the preferential chain motion parallel to the substrate. The degree of anisotropy was quantified by a combination of fluorescence recovery after photobleaching and neutron reflectometry, probing chain diffusion in directions parallel and perpendicular to the substrate, respectively. Chain mobility was controlled by ionic strength of annealing solutions and steric hindrance to ionic pairing of interacting po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 20 publications
4
77
0
Order By: Relevance
“…We observed that HDFs displayed a moderate preference for aligning with the direction in which the slides were dipped during the dip coating process (Figures 3B & 4). Cells without any preferential alignment would be expected to have an average orientation of 45° (Figures 3B & 4 & Supplementary Figure 2); however, we saw that HDFs on PEDOT-PSS-based multilayer films had an average orientation of 38.6° ± 1.5° (Figure 4A & E), whereas HDFs on PEDOT-S-based multilayer films had an average orientation of 35.3° ± 1.8° (Figure 4B & E), which is likely to be because the polymer chains were aligned during the dip coating process as is commonly observed for multilayer films prepared in this fashion [34], and fibroblasts are known to respond to features on such length scales [35,36]. Interestingly, electrical stimulation of HDFs on the conductive substrates led to an increase in their propensity to align with the direction of the DC current passed through the substrate (akin to their behavior when a DC current is passed through the culture medium) [37], and we found that HDFs on PEDOT-PSS-based multilayer films had an average orientation of 27.7° ± 1.7° (Figure 4C & E), whereas HDFs on PEDOT-S-based multilayer films had an average orientation of 32.1° ± 1.1° (Figure 4C & E).…”
Section: Resultsmentioning
confidence: 83%
“…We observed that HDFs displayed a moderate preference for aligning with the direction in which the slides were dipped during the dip coating process (Figures 3B & 4). Cells without any preferential alignment would be expected to have an average orientation of 45° (Figures 3B & 4 & Supplementary Figure 2); however, we saw that HDFs on PEDOT-PSS-based multilayer films had an average orientation of 38.6° ± 1.5° (Figure 4A & E), whereas HDFs on PEDOT-S-based multilayer films had an average orientation of 35.3° ± 1.8° (Figure 4B & E), which is likely to be because the polymer chains were aligned during the dip coating process as is commonly observed for multilayer films prepared in this fashion [34], and fibroblasts are known to respond to features on such length scales [35,36]. Interestingly, electrical stimulation of HDFs on the conductive substrates led to an increase in their propensity to align with the direction of the DC current passed through the substrate (akin to their behavior when a DC current is passed through the culture medium) [37], and we found that HDFs on PEDOT-PSS-based multilayer films had an average orientation of 27.7° ± 1.7° (Figure 4C & E), whereas HDFs on PEDOT-S-based multilayer films had an average orientation of 32.1° ± 1.1° (Figure 4C & E).…”
Section: Resultsmentioning
confidence: 83%
“…[21][22][23] There are some recent studies which have used the FRAP phenomenon to study diffusion of proteins in PEMs as well as inter-diffusion of the components of the PEM system within the multilayer stack. [24,25] These studies assumed an analytical model of fluorescence recovery which is (a) more appropriate for a closed system such as a cell and (b) assumed only diffusion to be the mechanism of recovery while ignoring other effects such as adsorption and desorption of the molecules to the PEM matrix. To increase the rigor in the analysis of FRAP data from thin films, we studied the transport of molecules in PEMs surrounded by an aqueous medium numerically, incorporating the effect of additional transport pathways such as the surrounding medium and considering the effect of finite film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The self‐roughening behavior of exponentially growing PEM films is essentially a pressure‐induced wrinkling behavior, which is caused by the diffusion of polyelectrolytes into the films during the assembling process . Since molecular diffusion can be affected dramatically by the presence of steric hindrance, the formation of surface wrinkles could be affected by changing the internal construction of these PEM films. In this study, we fabricated a self‐wrinkling PEM film capable of being covalently cross‐linked under UV light.…”
mentioning
confidence: 99%